Innovations in Latvian Sport Strategic Planning - Grāvītis, Uldis; Luika, Biruta; Luika, Signe (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Taking into account the importance of sport in the formation of physically and mentally healthy nation, and in the strengthening of national identity, the government of Latvia in 2004 has ratified Basic Statement for Sport Policy, including main directions of sport policy, its aims and sub goals, priorities, results to be reached and the directions of activity. To implement this Basic Statement, was worked out National Program for Sport development from 2006 to 2012.Soon this planning period will be completed and it is necessary to find out what to improve in next document of sport strategic planning.